Peran Komunikasi Penyuluhan Dalam Menyosialisasikan Program Keluarga Harapan (PKH) Di Desa Riding Panjang Kecamatan Belinyu - Satria, Anthony Lee Mega; Fikri, Zakiyudin; Sari, Sintia (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2025)
The Program Keluarga Harapan (PKH), or the Family Hope Program, is a conditional social assistance initiative targeting poor and vulnerable families listed in the integrated data system for handling the poor, who have been designated as beneficiary families of the program. The low level of public understanding regarding the benefits and objectives of the Family Hope Program has hindered the achievement of its intended goals. This study aims to examine the role of extension communication in disseminating information about the Family Hope Program (PKH) in Riding Panjang Village, Belinyu District. The research employed a qualitative descriptive method, using interviews with informants from recipient families of the PKH program. Data analysis was conducted descriptively. The results of the study indicate that there are obstacles in the community's comprehension of messages conveyed through the extension communication efforts. Moreover, community participation remains weak, especially in decision-making related to the Family Hope Program. Based on these findings, the study recommends that the government carry out regular evaluation and monitoring activities, and enhance the capacity of extension officers to ensure effective communication in delivering the objectives of the Family Hope Program.